Reflections of Information Sharing and Collaborative Innovation in the Social Responsibility of Cooperatives - Beuren, Ilse Maria; Santos, Vanderlei dos; Bernd, Daniele Cristina; Pazetto, Celliane Ferraz (Review of Business Management, 2020)
Purpose – This study analyzes the reflections of information sharing and collaborative innovation in the social responsibility, in its environmental, economic, and social dimensions, of cooperatives that form part of strategic alliances. Design/methodology/approach – A survey was conducted of managers of Brazilian agricultural cooperatives that have strategic alliances and 91 valid questionnaires were obtained. The data collected were analyzed through structural equation modeling. Findings – Information sharing had positive effects on collaborative innovation and the environmental dimension of social responsibility. No significant relationships were found between information sharing and social responsibility, in the economic and social dimensions, nor between collaborative innovation and social responsibility, in the environmental and economic dimensions. Originality/value – The main contribution of the research is to examine the links between information sharing, collaborative innovation, and social responsibility. The study provides empirical evidence that information sharing between cooperative partnerships favors the exploration of new knowledge/technologies. It also reveals that information sharing helps social responsibility in its environmental dimension by providing information that can contribute to reducing the environmental impact of the activities of cooperative alliances. However, it suggests that information sharing influences collaborative innovation and social responsibility in its environmental dimension, but not in its economic and social dimensions.